miR-144-5p and miR-451a Inhibit the Growth of Cholangiocarcinoma Cells Through Decreasing the Expression of ST8SIA4 - Fu, Wan; Yu, Guangcai; Liang, Junnan; Fan, Pan; Dong, Keshuai; Zhang, Bixiang; Chen, Xiaoping; Zhu, Hong; Chu, Liang (Frontiers in Oncology, 2021)
Accumulating evidences indicate that non-coding RNAs play crucial roles in the progression of an extensive range of carcinomas. This study aimed to investigate the action mechanism of miR-144-5p and miR-451a in cholangiocarcinoma. We found that miR-144-5p and miR-451a were significantly decreased in cholangiocarcinoma patient samples compared to the adjacent normal bile duct samples. The downregulation of these two miRNAs was correlated with a more advanced disease state of cholangiocarcinoma patients. Overexpression of miR-144-5p and miR-451a suppressed the proliferation, invasion and migration of cholangiocarcinoma cells in vitro and inhibited xenograft tumor growth. Knockdown of these two miRNAs had the opposite effects. miR-144-5p and miR-451a regulated the expression of ST8 alpha-N-acetyl-neuraminide alpha-2,8-sialyltransferase 4 (ST8SIA4), and presented a correlation with ST8SIA4 in patient samples. Overexpression of ST8SIA4 promoted the proliferation, invasion and migration of cholangiocarcinoma cells, and the changes were reversed by upregulating the expression of miR-144-5p and miR-451a. Our findings indicated that miR-144-5p and miR-451a displayed a tumor suppressor role through decreasing the expression of ST8SIA4 in cholangiocarcinoma.